Pengaruh Model Pembelajaran Talking Stick Terhadap Hasil Belajar Matematika Siswa di SD Negeri 094155 Rambung Merah - Iren; Hetdy Sitio; Aprido.B. Simamora (PIJAR: Jurnal Pendidikan dan Pengajaran, 2024)
The aim of this research is to determine the influence of the Talking Stick Learning Model on Student Mathematics Learning Outcomes at SD Negeri 094155 Rambung Merah. Based on the research results and discussions that have been described, the researcher can conclude that the Talking Stick learning model influences the learning outcomes of Class III students at SD Negeri 094155 Rambung Merah by conducting one group pretest-posttest. Based on the data, the values ​​before and after the treatment increased from 59.54 to 77.64. After carrying out a descriptive test using the paired t test which was tested by the researcher. Where the tcount value is = 13.36 with a significance level of 0.000 and tcount = 13.363 > t table = 2.080, then H0 and Ha are accepted. This shows that there is an influence of the Talking Stick learning model on Mathematics learning outcomes for class III students at SD Negeri 094155 Rambung Merah. Thus it can be stated that the score has experienced a significant increase in student learning outcomes so that Ha learning outcomes are accepted